Metabolic Effects of Dietary Proteins, Amino Acids and The Other Amine Consisting Compounds on Cardiovascular System. - Elif Uğur; Reyhan Nergiz Ünal (Turkish Journal of Agriculture: Food Science and Technology)
During the prevention and treatment of cardiovascular diseases, first cause of deaths in the world, diet has a vital role. While nutrition programs for the cardiovascular health generally focus on lipids and carbohydrates, effects of proteins are not well concerned. Thus this review is written in order to examine effect of proteins, amino acids, and the other amine consisting compounds on cardiovascular system. Because of that animal or plant derived proteins have different protein composition in different foods such as dairy products, egg, meat, chicken, fish, pulse and grains, their effects on blood pressure and regulation of lipid profile are unlike. In parallel amino acids made up proteins have different effect on cardiovascular system. From this point, sulfur containing amino acids, branched chain amino acids, aromatic amino acids, arginine, ornithine, citrulline, glycine, and glutamine may affect cardiovascular system in different metabolic pathways. In this context, one carbon metabolism, synthesis of hormone, stimulation of signaling pathways and effects of intermediate and final products that formed as a result of amino acids metabolism is determined. Despite the protein and amino acids, some other amine consisting compounds in diet include trimethylamine N-oxide, heterocyclic aromatic amines, polycyclic aromatic hydrocarbons and products of Maillard reaction. These amine consisting compounds generally increase the risk for cardiovascular diseases by stimulating oxidative stress, inflammation, and formation of atherosclerotic plaque.